(553) التقييم التجاري للمشروعات ومعايير الربحية التجارية (بيان كيفية حساب الربحية التجارية خلال حالة تطبيقية) Commercial evaluation of projects and commercial profitability criteria (Explanation of how to calculate commercial profitability through an applied case) - مصطفى الأروادي (معهد التخطيط القومي, 2026)
المذكرة دراسة تطبيقية مفصلة حول "التقييم التجاري للمشروعات ومعايير الربحية"، متخذاً من مشروع لإنتاج سماد اليوريا حالة دراسية. يبدأ الملف بتوضيح مراحل إعداد المشروع من الفكرة المبدئية إلى تقرير الصلاحية الفني والاقتصادي، مع التركيز على قياس الربحية المالية التي تهم المستثمر لاتخاذ قرار الاستثمار. ويستعرض الملف البيانات الأساسية للمشروع المقترح، بما في ذلك الاحتياجات الاستثمارية المقدرة بنحو 44 مليون دينار، وتكاليف التشغيل التي تعتمد بشكل أساسي على الغاز الطبيعي، وبرنامج الإنتاج والإيرادات المتوقعة طوال العمر الإنتاجي للمشروع البالغ 15 عاماً. أما الجزء التحليلي من الملف، فيركز على تطبيق معايير قياس الربحية المختلفة، مثل معدل العائد البسيط، وفترة الاسترداد، وصافي القيمة الحالية، ومعدل العائد الداخلي. وتظهر النتائج أن المشروع يتمتع بربحية عالية وسيولة نقدية ممتازة، حيث يسترد استثماراته في أقل من 5 سنوات من بدء التشغيل. كما يتضمن الملف تحليلاً للحساسية لاختبار قدرة المشروع على الصمود أمام تقلبات الأسعار أو زيادة التكاليف، ويختتم بتقديم مقترحات لتعديل هيكل التمويل عبر إدخال القروض لتعظيم العائد على رأس المال المملوك، مما يجعله مرجعاً منهجياً متكاملاً لتقييم الجدوى الاقتصادية للمشروعات الصناعية الكبرى. This memorandum is a detailed applied study on "Commercial Project Evaluation and Profitability Criteria," using a urea fertilizer production project as a case study. The document begins by outlining the project's development stages, from initial concept to technical and economic feasibility report, focusing on measuring financial profitability, which is crucial for investors making investment decisions. It presents the key data for the proposed project, including estimated investment requirements of approximately 44 million dinars, operating costs primarily based on natural gas, and the production schedule and projected revenues over the project's 15-year productive life.The analytical section of the document focuses on applying various profitability measurement criteria, such as the simple rate of return, payback period, net present value, and internal rate of return. The results demonstrate that the project enjoys high profitability and excellent cash flow, recovering its investment in less than five years from the start of operations. The document also includes a sensitivity analysis to test the project’s ability to withstand price fluctuations or increased costs, and concludes by offering proposals to modify the financing structure by introducing loans to maximize the return on equity, making it a comprehensive methodological reference for assessing the economic feasibility of major industrial projects.